Phytochemical research of study Thymus x citriodorus (Pers.) Schreb. var. «Silver Queen» - Steshenko, Yа. M.; Стешенко, Яна Миколаївна (Запорізький державний медичний університет, 2021)
Introduction. Analyzing the information search on phytochemical studies of plants, it was found that a large number of studies of plants are aimed at studying the qualitative and quantitative content of BAS in plant. Today, the specie of the genus Thymus x citriodorus (Pers.) Schreb. var. «Silver Queen» is poorly studied, but promising in terms of sufficient raw material base. It‘s gibrid. The diffusion of information on research and the application of the results of research is important. Species of the genus Thymus L. (Thyme), one of the most famous in this family, number about 400 members, of which up to 50 have been identified in the modern flora of Ukraine.